Biomechanics of balance: Paradigms and procedures - Hudson, J. L.; Spina, M.; Spence, J.; Ciapponi, T.; Christ, F.; Caldwell, A.; Cleary, T. (ISBS - Conference Proceedings Archive (Konstanz), 1995)
Balance, like coordination, is understood by virtually everyone to be a critical component of skillful movement. Yet there exists relatively little biomechanical research into how balance is employed and improved by performers of disparate abilities in different activities. One explanation for this dearth of research is that our traditional conceptions of balance may be too limiting if our goal is to measure and modify balance in the context of sports. With this goal in mind, I will review several definitions and conceptions of balance, elaborate and integrate some of these approaches, and propose a paradigm and procedures for assessing balance during physical activity